Catheter ablation of ventricular tachycardia in patients with postinfarction left ventricular aneurysm. (27th October 2021) - Amin, Mustapha; Farwati, Medhat; Hilaire, Emilie; Siontis, Konstantinos C.; Madhavan, Malini; Kapa, Suraj; Mulpuru, Siva K.; Deshmukh, Abhishek J.; Cha, Yong‐Mei; Friedman, Paul A.; Munger, Thomas; Asirvatham, Samuel J.; et al.
Abstract: Background: While ventricular tachycardia (VT) in the setting of postmyocardial infarction left ventricular aneurysms (LVA) is not uncommonly encountered, there is a scarcity of data regarding the safety, efficacy, and outcomes of ablation of VT in this subset of patients. Methods: Our study included consecutive patients aged 18 years or older with postmyocardial infarction LVA who presented to Mayo Clinic for catheter ablation of VT between 2002 and 2018. Results: Of 34 patients, the mean age was 70.4 ± 9.1 years; 91% were male. Mean LVEF was 29 ± 9.7% and left ventricular end‐diastolic dimension was 64.9 ± 6.6 mm. The site of the LVA was apical in 21 patients (62%). Fifteen patients (44%) presented with electrical storm or incessant VT. Nine patients (26%) had a history of intracardiac thrombus. All except for one patient had at least one VT originating from the aneurysm. The mean number of VTs was 2.9 ± 1.7. All patients underwent ablation at the site of the aneurysm. Ablation outside the aneurysm was performed in 13 patients (38%). Low‐voltage fractionated potentials and/or late potentials at the aneurysmal site were present in all cases. Complete elimination of all VTs was achieved in 18 (53%), while the elimination of the clinical VT with continued inducibility of nonclinical VTs was achieved in a further 11 patients (32%). Two patients developed cardiac tamponade requiring pericardiocentesis. During a mean follow‐up period of 2.3 ± 2.4 years, 11 patients (32%) experienced VT recurrence. Freedom from all‐cause mortality at 1‐year follow‐up was 94%. Conclusion: Radiofrequency catheter ablation targeting the aneurysmal site is a feasible and reasonably effective management strategy for clinical VTs in patients with postinfarction LVA.